(untitled) (Research, Society and Development, 2023)
The endodontic treatment is a procedure carried out in multiple sessions by two dentists. As the advent of technology, now the emergence of new instruments that will culminate in the realization of a faster procedure, in just one session. In view of this, the objective of the present study is to discuss the advantages and disadvantages of performing endodontic treatment in a single session, in addition to analyzing the benefits and complications, through a literature review. Foram selected 23 scientific articles in the Portuguese and English languages, collected between the years of 2012 and 2022 in the Scielo, PubMed and Google Scholar databases. Through two studies carried out, it can be observed that endodontic treatment in a single session decreased patient discomfort, work time and cost, in addition to minimizing the chance of contamination between procedures and reducing the occurrence of accidents and complications. Therefore, obtaining an incorrect diagnosis and inappropriate indication of this technique can result in disadvantages, such as exacerbated postoperative pain and failures. In this way, it is possible to conclude that the determination of treatment in a single or multiple session is a professional decision and should take into consideration the clinical characteristics of the case combined with scientific evidence, as well as the professional’s skills and available technologies.